Dionysos’ Labours. The Human Body in Classical Tragedy and its Political Relevance (Res Publica. Revista de Historia de las Ideas Políticas, 2017)
In this essay we reflect on the political significance of the human body in classical tragedy not only as a literary genre, but also as a kind of theatre which has enjoyed in modern times an extensive theatrical reception of live performances. In the first part, a clarification of the status of the tragic body in ancient tragedy is put forward, getting the perspective of the satyr drama as the closing element in the tetralogy, by means of which ancient playwrighters competed in theatrical contests in honor of Dionysos. In the second and third parts. two brief case studies of the modern receptions of two classical tragedies (Euripides’ Bacchae and Shakespeare’s Coriolanus) are offered in order to develop some ideas put forward in the first part.